Research on the Application of Value Creation of Big Data in Smart Tourism - Zhao, Yu; Zhan, Yanqing (International Journal of Emerging Trends in Social Sciences, 2019)
Against the background of the new era, the rapid progress of information science and technology represented by big data, cloud computing and Internet of things promotes the intelligent transformation of tourism industry. Based on the technical support of big data, it integrates tourism resources to generate value creation and apply it in smart tourism, and promotes the optimization and innovation of tourism at the level of marketing, service and management. In the context of informatization, the implementation of smart tourism has become the only way for the development of the tourism industry (Dai, P. ,2015). However, the application of big data in smart tourism also faces such problems as dense and miscellaneous information data, uneven level of information technology, lack of smart tourism big data professionals, and privacy data security (Yang, X.,2015). This paper discusses the development status and future direction of smart tourism in the context of big data, so as to boost the steady development of smart tourism relying on big data platform.